Forecasting Tourist Arrivals in the Riau Islands Province for 2026–2027 Using Macroeconomic Indicators and Google Trends Data (2010–2024) - Kurniawan, Welli Braham; Kurniawan, Fendy (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2026)
This study aims to analyze macroeconomic and digital factors influencing tourist arrivals in the Riau Islands Province and to develop a multiple linear regression-based prediction model. The research utilizes monthly time-series data from January 2015 to June 2024, covering variables such as Gross Domestic Product (GDP), inflation, Rupiah–US Dollar exchange rate, and travel interest index derived from Google Trends. The findings reveal that the developed model demonstrates high accuracy, with an Adjusted R² of 0.87 and a Mean Absolute Percentage Error (MAPE) of 6.85%. Partially, GDP and the Google Trends index have a positive and significant effect on tourist arrivals, while inflation and exchange rate fluctuations show a negative and significant impact. Based on the model, tourist arrivals in the Riau Islands are projected to reach 2.45 million in 2025 and 2.62 million in 2026. These results highlight the importance of maintaining economic stability and strengthening data-driven digital marketing strategies to foster the tourism sector’s growth in the post-pandemic era.